2013
DOI: 10.4049/jimmunol.1202351
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of T Cell Epitopes Implementing HLA-Peptidomics into a Reverse Immunology Approach

Abstract: T cell recognition of minor histocompatibility Ags (MiHA) plays an important role in the graft-versus-tumor effect of allogeneic stem cell transplantation. Selective infusion of T cells reactive for hematopoiesis-restricted MiHA presented in the context of HLA class I or II molecules may help to separate the graft-versus-tumor effects from graft-versus-host disease effects after allogeneic stem cell transplantation. Over the years, increasing numbers of MiHA have been identified by forward immunology approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 45 publications
(48 reference statements)
0
35
0
1
Order By: Relevance
“…By integrating exome sequencing, MHC peptide ligand prediction algorithms and targeted MS, Gubin et al recently identified tumor-specific mutant MHC class I peptides as targets of this form of immunotherapy (88). Proteogenomics approaches (139, 140) using DDA MS were also recently used for the identification of mutant as well as polymorphic MHC class I peptides (5,51,(141)(142)(143)(144). Notably, the detection of tumor-specific mutant MHC peptides has not been achieved yet using DIA MS.…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 99%
“…By integrating exome sequencing, MHC peptide ligand prediction algorithms and targeted MS, Gubin et al recently identified tumor-specific mutant MHC class I peptides as targets of this form of immunotherapy (88). Proteogenomics approaches (139, 140) using DDA MS were also recently used for the identification of mutant as well as polymorphic MHC class I peptides (5,51,(141)(142)(143)(144). Notably, the detection of tumor-specific mutant MHC peptides has not been achieved yet using DIA MS.…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 99%
“…45 PBMCs were incubated with PE-labeled pMHC tetramers for 1 hour at 4°C. Cells were washed twice and incubated with anti-PE magnetic microbeads (Miltenyi Biotec, Bergisch Gladbach, Germany).…”
Section: Generation Of Peptide-mhc Complexesmentioning
confidence: 99%
“…Ultimately, this improved knowledge of mHags may lead to superior identification strategies through the design of algorithms directed towards the computational prediction of true immunotherapeutic mHags. 11,32,33 In conclusion, the new approach integrating all variations of the 1000 Genomes Project currently represents the most attractive method for highly efficient mHag identification. This methodology will conceivably facilitate the identification of the broad set of mHags that are not only necessary for the optimal setup of mHag-based immunotherapy trials, but also for a better understanding of mHag immunobiology.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic bases of these polymorphisms are either single nucleotide polymorphisms (SNPs), base-pair insertions or deletions (indels) or copy number variations (CNVs). 11 In the mid-1990s, the discovery that a specific set of mHags is solely expressed on malignant and non-malignant hematopoietic cells, shifted the paradigm on mHags and suggested that hematopoietic-restricted mHags could be ideal targets for separating GvT from GvHD. 1,12,13 Nonetheless, a thorough clinical evaluation of this attractive concept has not yet been realized, because the small number of genuinely hematopoietic system-specific mHags identified so far permits the inclusion of not even 20% of the transplant patients in the slow-running clinical trials.…”
Section: Introductionmentioning
confidence: 99%